Application of safeguards to nuclear submarine fuel to ensure security and proliferation resistance (Revista da EGN, 2024)
The utilization of nuclear energy has long played a pivotal role in advancing the capabilities of naval fleets worldwide, particularly in the domain of nuclear-powered submarines. However, the management and safeguarding of nuclear submarine fuel have emerged as critical concerns in the context of global security, non-proliferation efforts, and environmental responsibility. This article delves into the intricate landscape of safeguarding nuclear submarine fuel, addressing the multifaceted  challenges and proposing innovative solutions to enhance security and proliferation resistance.